Behavioral Competence as a Positive Youth Development Construct: A Conceptual Review - Hing Keung Ma (The Scientific World Journal)
Behavioral competence is delineated in terms of four parameters: (a) Moral and Social Knowledge, (b) Social Skills, (c) Positive Characters and Positive Attributes, and (d) Behavioral Decision Process and Action Taking. Since Ma’s other papers in this special issue have already discussed the moral and social knowledge as well as the social skills associated in detail, this paper focuses on the last two parameters. It is hypothesized that the following twelve positive characters are highly related to behavioral competence: humanity, intelligence, courage, conscience, autonomy, respect, responsibility, naturalness, loyalty, humility, assertiveness, and perseverance. Large-scale empirical future studies should be conducted to substantiate the predictive validity of the complete set of these positive characters. The whole judgment and behavioral decision process is constructed based on the information processing approach. The direction of future studies should focus more on the complex input, central control, and output subprocesses and the interactions among these sub-processes. The understanding of the formation of behavior is crucial to whole-person education and positive youth development.